Inner screening corrections to the Debye interaction in hot/dense plasmas in the vicinity of the bound – free transitions - C. Deutsch; G. Naouri; N. A. Tahir (Physical Sciences and Technology, 2020)
Considering hot/dense plasmas strongly ionized and still retaining hydrogenic bound states (1 ≤ z ≤ 6), we focus attention on the delocalization features of ion-electron orbitals, such as wide spreading and attending of pertaining wave functions close to the free bound transition. A systematic embedding process of increasingly excited states is shown to introduce short-range corrections to the Debye potential, while highlighting blue line shifts relative to initial Debye data. D-Dependence of a ion-electron dipole bound in a Debye potential evaluated. The probability of presence r2 R2nl (r) of the electron around its bounding ion are plotted. Orbitals 1S and 2S in a 3-component hydrogen plasma with T = 8.62 eV and ne =2.24x1023 cm-3 are calculated. A classical – partially degenerate difference is shown. Normalized solutions to quantum – mechanical equation for partially ionized hydrogen are obtained. Also levels deeply involved in the bound-free transition, close to vanishing in the continuum are shown.